2018
DOI: 10.3892/ol.2018.7794
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight polysaccharides from Agaricus�blazei Murrill modulate the Th1 response in cancer immunity

Abstract: To assess the effect of low-molecular-weight polysaccharides from Agaricus blazei Murrill (ABP-AW1) as an immunoadjuvant therapy for type 1 T-helper (Th1) responses in tumorigenesis, C57BL/6 mice were inoculated subcutaneously with ovalbumin (E.G7-OVA). After 3, 10 and 17 days, the mice were immunized with PBS, OVA alone, or OVA and ABP-AW1, at low (50 µg), intermediate (100 µg) or high (200 µg) doses. Tumor growth was examined and compared among the groups, as were the following parameters: Splenocyte viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The CD4 + T cell response plays an important role in generating the optimum antibody responses to the FMD vaccine in cattle [50]. It was reported that the ratio of CD4 + /CD8 + T lymphocytes was increased when mice were inoculated with OVA in combination with polysaccharides from Agaricus blazei Murrill [51]. In this study, a significantly higher ratio of CD4 + /CD8 + T cells was detected in the SO-VE-GS group as compared with either the control (antigen in saline) or the ISA 206 group, which indicates that more CD4 + T cells were activated in the SO-VE-GS group.…”
Section: Discussionmentioning
confidence: 99%
“…The CD4 + T cell response plays an important role in generating the optimum antibody responses to the FMD vaccine in cattle [50]. It was reported that the ratio of CD4 + /CD8 + T lymphocytes was increased when mice were inoculated with OVA in combination with polysaccharides from Agaricus blazei Murrill [51]. In this study, a significantly higher ratio of CD4 + /CD8 + T cells was detected in the SO-VE-GS group as compared with either the control (antigen in saline) or the ISA 206 group, which indicates that more CD4 + T cells were activated in the SO-VE-GS group.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows that coculture of pulsed DCs with primary T-lymphocytes induces the release of TNF α , IFN γ , and IL-2, while IL-5 and IL-4 release were not detected. The secretion of TNF α , IFN γ , and IL-2 is associated with a Th1 phenotype [41], which promotes an antitumor immune response [42].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we proposed that aP-GSe-enhanced Th1 and Th2 immune responses might be attributed to the JAK-STAT pathways underlying. The ratio of CD4 + /CD8 + is usually used to evaluate the immune status of the body, and higher CD4 + /CD8 + ratio indicates a stronger immune status [66,67]. Yang et al found that inoculation with foot-and-mouth disease (FMD) vaccine leads to higher immune response and CD4 + /CD8 + ratio of lymphocytes in young sires [68].…”
Section: Discussionmentioning
confidence: 99%